2008
DOI: 10.1002/bit.21786
|View full text |Cite
|
Sign up to set email alerts
|

Effect of humic acids on electricity generation integrated with xylose degradation in microbial fuel cells

Abstract: Pentose and humic acids (HA) are the main components of hydrolysates, the liquid fraction produced during thermohydrolysis of lignocellulosic material. Electricity generation integrated with xylose (typical pentose) degradation as well as the effect of HA on electricity production in microbial fuel cells (MFCs) was examined. Without HA addition the maximum power density increased from 39.5 mW/m(2) to 83 mW/m(2) when initial xylose concentrations increased from 1.5 to 30 mM, while coulombic efficiency ranged fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(33 citation statements)
references
References 30 publications
1
31
0
1
Order By: Relevance
“…Comparing the changes in three-dimensional fluorescence spectra and electricity production, it could be found that the change in humic-like substances showed a positive correlation with the electricity production of the MFC. The results for the humic-like substances are similar to those of Thygesen et al [40] and Huang and Angelidaki [41], who found that humic acid could enhance the electricity production of MFC because it could act as mediator.…”
Section: Changes In Sludge In the Anode Chambersupporting
confidence: 86%
“…Comparing the changes in three-dimensional fluorescence spectra and electricity production, it could be found that the change in humic-like substances showed a positive correlation with the electricity production of the MFC. The results for the humic-like substances are similar to those of Thygesen et al [40] and Huang and Angelidaki [41], who found that humic acid could enhance the electricity production of MFC because it could act as mediator.…”
Section: Changes In Sludge In the Anode Chambersupporting
confidence: 86%
“…The power density generated by the devices was calculated by Pd=VI/A; where, V is the voltage; I is the current and A is the anode surface area (Huang and Angelidaki, 2008a). Both efficiency of electron transfer to the anode surface (coulombic efficiency (εcb)) and substrate degradation rate (SDR) were calculated as explained by Huang and Angelidaki (2008b), Mohan et al (2008) and Antonopoulou et al (2010).…”
Section: Mfc Designmentioning
confidence: 99%
“…Chemical and biological approaches to sustainable energy production from the liquefied hydrolysates to energy carriers, such as methane, ethanol, and H 2 , have been developed. However, many of these approaches encounter technical and economical hurdles (10,12,15,16). An alternative strategy is direct conversion of wheat straw biomass to electrical energy in microbial fuel cells (MFCs).…”
mentioning
confidence: 99%
“…MFCs are bioelectrochemical reactors in which microorganisms mediate the direct conversion of chemical energy stored in organic matter or bulk biomass into electrical energy (12,15,16,40). Various substrates, such as simple carbohydrates, lowmolecular-weight organic acids, starch, amino acids, chitin, cellulose, domestic wastewater, food-processing wastewater, recycled paper wastewater, and marine sediment organic matter, have been successfully utilized for power generation in MFCs (16-18, 27, 30, 33).…”
mentioning
confidence: 99%